PENGARUH DIMENSI SELF DIRECTED LEARNING (SDL) TERHADAP KETAHANAN FISIK KELUARGA WANITA KARIER DI KOTA TASIKMALAYA - Lesi Oktiwanti, Siti Mariam, Lulu Yuliani, Lilis Karwati Dede Nurul Qomariah (Jurnal Eksistensi Pendidikan Luar Sekolah (E-Plus), 2020)
PENGARUH DIMENSI SELF DIRECTED LEARNING (SDL) TERHADAP KETAHANAN FISIK KELUARGA WANITA KARIER DI KOTA TASIKMALAYA 1)Lesi Oktiwanti,2)Siti Mariam, 3)Lulu Yuliani, 4)Lilis Karwati, 5)Dede Nurul Qomariah 1,2,3,4,5Jurusan Pendidikan Masyarakat, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Siliwangi 1)lesioktiwanti@unsil.ac.id, 2)mariammarzha@gmail.com, 3)luluyuliani@unsil.ac.id, 4)liliskarwati@unsil.ac.id, 5)dnurul@unsil.ac.id ABSTRAK The self-directed learning process undertaken by career women includes planning, setting goals and implementing self-directed learning to maintain the physical resilience of the family. The purpose of this study was to determine the effect of the dimensions of Self Directed Learning (SDL), namely the dimensions of the person, process and context on the physical resilience of career women families. The variables in this study consisted of independent variables namely the person dimension (X1), the process dimension (X2) and the context dimension (X3), and the dependent variable was the physical resilience of the family (Y). The research method used was descriptive analysis with data collection techniques using a questionnaire to 100 career women as samples with 4,024 populations (ɛ 10%) spread over ten subdistricts in Tasikmalaya City. The analysis technique used in this study is multiple regression analysis techniques with three predictors. Hypothesis testing uses simultaneous or joint F tests and partial t tests or individually between variables and looks for the value of the coefficient of determination using R square. The results of this study indicate that the dimension of Self Directed Learning (SDL) simultaneously influences and significantly affects the physical resilience of the families of career women in the City of Tasikmalaya by 36.5%. Partially the most influential dimension on the physical resilience of a career woman's family is the context dimension. Keywords: Family Physical Resilience, Self Directed Learning, Career Women.